L’héroïsme au féminin : réécriture des codes dans Pamphilia to Amphilanthus de Lady Mary Wroth - Pascal Caillet (Revue LISA)
Lady Mary Wroth (c.1587-c.1651/53) was probably the most important woman writer of her time. Daughter of poet Robert Sidney, niece to Philip Sidney and his sister the Countess of Pembroke, she was notably the author of the first Petrarchan sonnet sequence staging a female voice written by an Englishwoman, Pamphilia to Amphilanthus (1621). Following Philip Sidney’s manner in Astrophil and Stella, Mary Wroth’s sequence consists in 103 sonnets and songs representing the canzoniere addressed by Pamphilia to her lover Amphilanthus. Because of the considerable influence of her family on the literary production of their time, Mary Wroth’s works in prose as well as verse have often been compared to those of her father and aunt, but most of all to those of her uncle. The interplay between their works is vast and complex. This article aims at studying the play on the names of the protagonists of Pamphilia toAmphilanthus in relation to Philip Sidney’s and Robert Sidney’s poems, so as to illustrate the possible intertextual relationships which may be at work between these three poets.